Study on coupling effect of TLP-type FOWT with flex-joints - Meng, X.; Liu, M.; Li, Y.; Chu, D.; Wu, Changzhi (2017)
Copyright © 2017 by the International Society of Offshore and Polar Engineers (ISOPE). This paper studies the integral responses of tension leg platform movement with the coupled tower. Connection modes of tendons, such as flex-joints and clamped connections are investigated. The idealization of generalized single degree of freedom system for a floating offshore wind turbine with tension leg platform foundation is put forward to illustrate dynamic properties of the support structure. Optimization design aiming at avoiding resonance of wind turbines and sum-frequency of wave excitation is applied to define principal dimensions of the optimal model in moderately deep water. Assuming certain environmental conditions and equivalent loads of the 5.0MW wind turbine, transient dynamic analysis of the optimal structure is carried out to demonstrate responses of the foundation full or half coupled with the tower. It is found that in moderately deep water around 100m, the coupling effect of the tower and types of connections of tendons are not negligible. This study would serve as a reference of optimization analysis of the appropriate offshore wind turbine support structures.